2001
DOI: 10.1089/104303401753153956
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Study of Aerosolized Administration of tgAAVCF to Cystic Fibrosis Subjects with Mild Lung Disease

Abstract: Cystic fibrosis (CF) is one of the most common autosomal recessive disorders in North America, leading to significant morbidity and early mortality. The defect in the cystic fibrosis transmembrane conductance regulator protein (CFTR) function can be corrected in vitro by gene replacement with a wild-type gene. A Phase I, single administration, dose escalation trial was designed and executed to assess safety and delivery of tgAAVCF, an adeno-associated virus (AAV) vector encoding the human CFTR cDNA, by nebuliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
134
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(140 citation statements)
references
References 36 publications
5
134
0
1
Order By: Relevance
“…AAV is an attractive candidate for gene therapy. [32][33][34][35] There are many serotypes of AAV. Among them, AAV2 is the most popular one for scientific research.…”
Section: Discussionmentioning
confidence: 99%
“…AAV is an attractive candidate for gene therapy. [32][33][34][35] There are many serotypes of AAV. Among them, AAV2 is the most popular one for scientific research.…”
Section: Discussionmentioning
confidence: 99%
“…It is, nonetheless, tempting to speculate that at the very least, the therapeutic vector dosage could be reduced by a log to overcome problems associated with vector load and immune response seen in clinical trials. 35 Furthermore, given that AAV2 remains the sole serotype vector currently in use in human gene therapy, 20,21,[36][37][38][39][40] coupled with the fact that it is also the best characterized in terms of vector toxicology, it is conceivable that this strategy could be employed to augment transgene expression scAAV2-TC-PTP and scAAV2-PP5 as helper viruses for ssAAV2 vectors GR Jayandharan et al from single-stranded vectors containing large genes such as coagulation factor VIII in the liver in clinical trials in patients with hemophilia A. In our current studies, the TC-PTP and the PP5 genes were under the control of the RSV promoter.…”
mentioning
confidence: 99%
“…However, vector-specific mRNA could not be detected and therefore evidence for gene transfer was not provided. 5 In summary, these new studies consolidate the view that proof-of-principle of gene transfer can be demonstrated in some, but not all studies, but that gene transfer efficacy is currently insufficient to warrant phase II/III trials. Thus, significant improvements in all aspects of gene transfer need to be made.…”
Section: Five Clinical Trials For Cf Have Been Carried Out Between 20mentioning
confidence: 65%